An exploratory study of adaptation to physical disabilities of selected cheerleading participants - Manalo, Rod Vincent P. 1999-; Dimarucut, Alberto L. DSD. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2023)
With the growing interest in cheerleading, literature about ParaCheerleading or Adaptive Abilities is still very limited. This study sought to explore the adaptation to physical disabilities of selected cheerleading participants in training and performance. There were two parts to the data collection in the study: data from the survey and data from the interview. Twenty four (N=24) cheerleaders from five selected universities answered a survey to identify the prevalence of disabilities among cheerleaders. A cheerleader with a disability (CWD) was the main participant for the interview: moreover, his coach and three of his teammates were also interviewed to further explore the adaptation. Additionally, the data from the interview were analyzed using narrative analysis, through an inductive and deductive approach. Results of the survey showed that most cheerleaders have had visual impairments along with their teammates; in addition to this, most of them use contact lenses or reading glasses as assistive devices. Meanwhile, the SEMA model helped reveal three phases of the interview, namely: recruitment, training and performance, and meaning. Thus, the cheerleader with a disability’s background and skills, as well as having a supportive environment within the team, were significant factors and paved the way for adaptation in training and performance of the participant, as it was clear that the cheerleader with a disability's adaptation depended on the ecological factors mentioned by Hutzler’s SEMA.
Vita
Thesis (Bachelor of Sport Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Cheerleading; Dance for people with disabilities